Internet use and pro-environmental behavior: Evidence from China - Xiao, Youzhi; Liu, Xuemin; Ren, Ting (PloS one, 2022)
Solving environmental problems relies upon cultivating pro-environmental behavior in the society. While the internet has been widely used to facilitate information transmission and communication, it’s important to understand its function in promoting pro-environmental behavior. Using the data from the China General Social Survey 2013, the relationship between the use of internet and the individual’s pro-environmental behavior is investigated, and overall positive effects are found. The results show that, the influence of internet use is more pronounced on the private pro-environmental behavior when further dividing pro-environmental behavior into private and public types. Moreover, the positive effect of internet use on pro-environmental behavior is more pronounced among low-income and female groups, compared to middle to high income and male counterparts, respectively, when considering the heterogeneity across different groups of individuals. We further explore the plausible channels of providing information, encouraging participation in pro-environmental campaigns and improving social relationships through which internet use facilitates pro-environmental behavior.